Feasibility and preliminary findings of a bacterial diversity study in periodontitis: a pilot investigation from the Western Cape - Kabbashi, Salma; Prince, Yvonne; Ngwa, Ndonwi Elvis; Holmes, Haly; Davison, Glenda Mary; Davids, Saarah F. G.; Chetty, Manogari (Frontiers in Oral Health, 2025)
IntroductionPeriodontitis is a significant health challenge caused by a complex interaction between bacterial infection, host immune response, and environmental factors, leading to tooth loss, bone loss, and potential associations with major systemic diseases and conditions. While the determinants of periodontitis have been extensively investigated in other populations, such studies are lacking in South Africa, which represents a high-risk population. Therefore, this study was conducted to characterize the subgingival bacterial biodiversity in the periodontal pockets of patients with periodontitis in a Western Cape population.Materials & methodsPooled subgingival plaque samples were collected from the deepest pocket/crevices of five periodontitis cases and five controls using sterile paper points. Illumina MiSeq paired-end sequencing and QIIME2 software were employed for sequence filtration and analysis. Several alpha and beta-diversity metrics assessed biodiversity within-sample and population structure between different microbiota datasets, respectively. Statistical significance for alpha diversity was tested using the Kruskal–Wallis H test (p < 0.05), and beta diversity differences were evaluated using PERMANOVA. Data visualization, including beta diversity plots, was conducted with the Phyloseq package in R.ResultsBeta-diversity measures revealed significant differences between periodontitis cases and controls (p-value = 0.04), whereas alpha-diversity was higher in cases, though without statistical significance (p-value ≥ 0.05). Cases group showed high relative abundance of Fusobacterium (16%), Porphyromonas (10%), and Treponema (9%), while the periodontally healthy controls were dominated by Streptococcus (20%), Fusobacterium (15%), and Veillonella (10%), with g_Streptococcus showing a significant difference (p-value = 0.008). Differential abundance analysis revealed distinct bacterial genera enriched in cases (Bulleidia, Peptoanaerobacter, Phocaeiola, W5053) and controls (Abiotrophia, Haemophilus, Lautropia, Rothia, Streptococcus). Sample-specific variations included higher levels of Porphyromonas (15%) in grade B and Fusobacterium (20%) in grade C.ConclusionThis exploratory study highlights distinct bacterial communities associated with periodontitis in a South African population. The findings emphasize the need for larger, population-based cohorts to validate these results and lay a foundation for future research into region-specific microbial profiles and their implications for personalized treatment strategies.